User's Manual for GeogridBridge 3. 0: A Guide to the Load Displacement Compatibility Method (LDC) for Design of Column-Supported Embankments - P. McGuire, Michael; G. Hummel, Elise; M. Hunstein, Eric; A. Sloan, Joel (American Society of Civil Engineers, 2024)
This book guides engineers on how to use the GeogridBridge 3.0 (GGB3) spreadsheet, which utilizes the Load Displacement Compatibility (LDC) method for the design of column-supported embankments (CSEs) and walks through two worked examples to illustrate the use of the spreadsheet.